2009
DOI: 10.1002/cne.22007
|View full text |Cite
|
Sign up to set email alerts
|

Synapse‐to‐synapse variation in mean synaptic vesicle size and its relationship with synaptic morphology and function

Abstract: Synaptic vesicle (SV) size is one parameter that controls the amount of neurotransmitter released from individual SVs and, therefore, is fundamental to our understanding of synaptic function. The recently discovered variability of mean SV size among excitatory hippocampal synapses -- if actively regulated -- is a potential mechanism for the regulation of transmitter release. Here, we investigated which parameters influence mean SV size. First, we revealed that synapse-to-synapse variability of SV size is a gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 38 publications
9
57
0
1
Order By: Relevance
“…To quantitatively address the size of labeled vesicles, we measured the area of typical electron lucent SVs and calculated the surface of these vesicles assuming they are spheres. As in previous reports (21,22), we found that SVs have an average diameter of 40 nm and a surface of 5,000 nm 2 . Next, we measured the area of labeled vesicles in synaptic profiles and found that labeled vesicle surfaces ranged from 5,000 to 20,000 nm 2 .…”
Section: Significancesupporting
confidence: 89%
See 1 more Smart Citation
“…To quantitatively address the size of labeled vesicles, we measured the area of typical electron lucent SVs and calculated the surface of these vesicles assuming they are spheres. As in previous reports (21,22), we found that SVs have an average diameter of 40 nm and a surface of 5,000 nm 2 . Next, we measured the area of labeled vesicles in synaptic profiles and found that labeled vesicle surfaces ranged from 5,000 to 20,000 nm 2 .…”
Section: Significancesupporting
confidence: 89%
“…Because we could not detect a significant amount of coated vesicles that could support membrane retrieval after the release of the RRP, it seems likely that SV retrieval via coated pits and coated vesicles does not play a major role at hippocampal synapses at least not under our experimental conditions. On the other hand, there is overwhelming evidence that clathrin plays a central role in SV retrieval at hippocampal synapses (6,9,22). The lack of coated vesicles in our samples may suggest a function of clathrin in noncoated vesicle endocytosis.…”
Section: Discussionmentioning
confidence: 68%
“…Presynaptic boutons of excitatory synapses contain round, clear vesicles ( 35 nm diameter) loaded with the neurotransmitter glutamate (Harris and Sultan 1995;Qu et al 2009). Vesicles distributed throughout the presynaptic bouton compose a "reserve" pool distinct from the anatomically docked vesicles that contact the presynaptic membrane at the AZ (Fig.…”
Section: Vesicles In Axonal Boutonsmentioning
confidence: 99%
“…Moreover, the presence of A␤ peptides in the synapses in vivo caused a dysfunction in synaptic vesicles with a diameter of ϳ40 nm (36). Because the binding of A␤ peptides to a membrane and the subsequent deformation are a linked phenomenon, the presence of deformed membranes may accelerate the binding and fibrillation of A␤.…”
mentioning
confidence: 99%